Polyvagal theory: a journey from physiological observation to neural innervation and clinical insight - Porges, Stephen W. (Frontiers in Behavioral Neuroscience, 2025)
Polyvagal theory (PVT) offers an integrative model of autonomic regulation that accounts for the evolution, neuroanatomy, and functional organization of the vagus nerve in relation to behavioral and emotional processes. This article revisits PVT by synthesizing its scientific foundations with recent advancements in transcriptomics, neurophysiology, and clinical application. Particular emphasis is placed on the theory's hierarchical model of the autonomic nervous system, the role of the ventral vagal complex in social behavior, and the construct of neuroception—the neural process by which safety and threat are detected without conscious awareness. The discussion incorporates both theoretical refinement and empirical validation while addressing common misconceptions and critiques of the model. In addition to the scientific narrative, the author offers a personal perspective on the intellectual and experiential origins of PVT, illustrating its translational value in clinical and therapeutic settings. By combining rigorous science with experiential insight, this article seeks to advance understanding of the autonomic foundations of social behavior and mental health.